Effect of rapid weight loss on metabolism and isokinetic performance capacity. A case study of two well trained wrestlers - Oopik, V.; Paasuke, M.; Sikku, T.; Timpmann, S.; Medijainen, L.; Ereline, J.; Smirnova, T; Gapejeva, E. (The Journal of Sports Medicine and Physical Fitness, 1996)
The effect of rapid weight loss on metabolism and isokinetic performance of quadriceps femoris muscle in two well-trained wrestlers was investigated. Weight reduction by 5.1-5.8% during 3 days resulted in reduction of plasma volume by 7.4-14.8% and increase in blood urea concentration by 1.8-2.1 times. Blood lactate response to standardized 5-min isokinetic performance test exercise was not dependent on body weight status. Peak torque, time to peak torque, rate of peak torque development and maximal power output measured during single maximal contraction of the quadriceps femoris muscle, as well as muscle working ability measured during 5-min isokinetic performance test were all impaired as a result of weight reduction. Body weight of the subjects, plasma volume, blood urea concentration and muscle isokinetic performance characteristics did not return to the initial levels even after 16.5-hrs recovery period (with food and drink ad libitum) following weight loss. These findings suggest that rapid weight loss by ca 5-6% may interfere wrestlers' metabolism and impair the quadriceps femoris muscle function. Moreover, 16.5-hrs recovery period with food and drink loading may be not sufficient to eliminate the negative consequences of body weight manipulation.